Potential of decentralized interbank settlements using blockchain - V. L. Dostov (Real Economics Publishing House, 2018)
Digital currency became a relevant topic lately, with the central banks contemplating the idea of issuing their own virtual currencies. Central banks may issue their virtual currencies to simplify interbank cross-border settlements and make them cheaper. In order to achieve this, both commercial and central banks recognize these virtual currencies as means of payments. In these projects blockchain could be used to store information about the digital currencies, instead of fiat money. We have identified the risks associated with the virtual currencies issued by the central banks: conversion and volatility risks. We have looked at different approaches to the distributed ledger, principles for decentralized virtual currencies, possibility of these technologies being used by the central banks, various risks and their mitigation strategies. We also formulated the technological and legal principles that may guide the issuance of the digital currency by the central banks. And reviewed the practicability of issuing virtual currencies by the central banks, based on exogenous and endogenous factors.